The impact of communication challenges toward international students’ learning sustainability - Aarthi, Muniandy (2022)
Many Higher Education Institutions throughout the world, including in Malaysia, are increasingly focusing on internationalisation. However, in private university settings, the challenges facing by international students are intercultural and language challenges towards learning sustainability. The purpose of this study was to look at the impact of communication challenges towards international student’s learning sustainability in Malaysian Higher Education Institutions. The information was gathered through a survey of 106 international students of a private university in Malaysia which was analysed using SPSS. Both intercultural challenges and language challenges exhibited significant negative relationship toward learning sustainability, which the intercultural challenges show greater impact than language challenges. The contributions and the implications of the study are discussed.